Unveiling the effects of post-harvest hydration treatments on physical and engineering properties of different varieties of paddy - Sharma, Sakshi; Semwal, Anil Dutt; Wadikar, Dadasaheb (ORYZA-An International Journal of Rice, 2023)
Effect of hot water hydration treatments at 70, 75 and 80 °C were studied on physical and engineering properties in 13 rice varieties differing in physico-chemical characteristics. Results revealed considerable effects of hydration temperatures on expression of traits understudy. Maximum percent change of the attributes over the control was observed at 80 °C. Top three characters that exhibited higher percent gain at 80 °C were angle of repose (15.17 %), bulk density (10.96 %), and tapped density (9.57 %), while top three characters exhibiting more reduction were Carr's Index (-8.21 %), equivalent diameter (-6.72 %), and L/B ratio (-5.92 %). Gravimetric and engineering properties depicted a linear relationship with hydration temperature. Intermediate and high amylose rice varieties were found to be more responsive to hot water hydration treatment. Principal Component Analysis (PCA) carried out with both i.e., control treatments and hydrated treatments at 80°C separately. In both the cases, first four principal components could explain 89.91 and 91.58 percent variation, respectively. The PCA-Biplot analysis grouped 13 varieties in four groups and 20 characters in three quadrants with changed composition, suggesting change in the expression of different characters due to the effect of hydration treatments. These results advocated the need for variety specific optimum hydration treatment recommendations for achieving desired output, which will aid in understanding the processing of Indian paddy varieties that possess wide variation in physico-chemical properties.